Pesantren and Gender Issues: Reinterpreting Classical Fiqh to Address Contemporary Gender Equality Challenges - Nasution, Suryadi; Pohan, Ali Jusri; Khairurrijal, Khairurrijal (Jurnal Pendidikan Islam, 2025)
The growing urgency of gender equality issues in Islam, which often conflict with textual interpretations of classical fiqh texts such as Fath al-Muin and I’anah al-Thalibin. Pesantrens, as traditional Islamic educational institutions, have the potential to become spaces for reinterpreting these texts in response to contemporary challenges. This study aims to explore how Pesantren Ma’had Darul Ikhlas in Mandailing Natal reinterprets classical fiqh by integrating local values, particularly the matrilineal culture that places women in a central role. The research employs a qualitative approach using ethnographic techniques and textual analysis, involving participant observation, in-depth interviews, and documentation. The findings reveal that the reinterpretation of classical fiqh is carried out through negotiations between the pesantren’s scholarly traditions, local culture, and modern social realities. For instance, the principle of justice in QS An-Nisa: 7 is used to support more inclusive inheritance practices for women, while the concept of qiwamah is understood as shared responsibility rather than male dominance. However, this reinterpretation still faces resistance from conservative groups and is hindered by the scarcity of progressive literature. The contribution of this research lies in its effort to enrich the discourse on the reinterpretation of fiqh in Islam by highlighting the flexibility of pesantrens in addressing modern challenges. Practically, these findings can serve as a reference for other pesantrens to open discussions on gender equality without abandoning their scholarly traditions.